Communication Patterns of Ethnic Chinese Traders with Ethnic Sundanese Employees - Sugiarta, Nugraha; Putri, Shinta Hartini; Hanifan, Lutfi; Reza, Faisal; Lestari, Anggita (Yayasan Sinergi Kawula Muda, 2024)
In the city of Bandung there are Ethnic Chinese who spread throughout the central point of trade to sell by employing Ethnic Sundanese. The object of this research is the communication pattern of Chinese ethnic traders with Sundanese ethnic employees in the Cibadak Shopping Center, Bandung City. The purpose of this research is to find out the communication process, communication barriers and find out the reasons why face negotiation is needed between Chinese ethnic traders and Sundanese ethnic employees at the Cibadak Shopping Center in Bandung City. This research uses qualitative methods and a case study approach. The data collection techniques used were interviews and observations to Chinese ethnic merchants and Sundanese ethnic employees. Data analysis techniques use data collection, data reduction, data display, and conclusion drawing. Data validity techniques use source triangulation. The results of this study reveal that the communication pattern used is circular communication, traders and employees apply facework theory where both parties respect each other, solidarity facework where both parties accept each other's existence, sensitivity facework where there is involvement of both parties in various social activities that occur, not just in work activities. The barriers that occur are barriers in terms of language, where there are differences in language backgrounds used by both parties. Face negotiations between ethnic Chinese traders and ethnic Sundanese employees are carried out to build good and smooth communication between the two parties.